Praia de Iracema e a revitalização de seu patrimônio histórico - Costa, Sabrina Studart Fontenele (Pós. Revista do Programa de Pós-Graduação em Arquitetura e Urbanismo da FAUUSP, 2005)
Iracema beach developed following the installation of a port designed to export products from the state of Ceará; in spite of not being part of the social life happening in downtown Fortaleza, it was fundamental for the economic growth of this city. When the port moved to another area of the city, some of its buildings - warehouses and trading offices associated with the port activities - were abandoned. Only in the mid 90s did the local government invest heavily in this area, building large projects that changed the area's spatial characteristics. In 1998, the state of Ceará government, encouraged Programa Cores da Cidade (Colors of the City Program) to renovate several historical buildings in an effort to consolidate its achievements in this area. Thus, part of the architectural patrimony had its façades restored and the interiors refurbished for new uses, mainly leisure and tourism activities. The renovation of the old buildings brought intense property speculation, which caused some of the former residents (mostly artists) to move away and attracted bars, restaurants and nightclubs. These new activities helped shape Iracema beach into the largest tourism hub in Fortaleza. This article provides an overview of the treatment given the architectural patrimony in the old port area of Fortaleza.